The Structure and Near-Bottom Magnetic Anomaly Characteristics of the Daxi Vent Field on the Carlsberg Ridge, Northwestern Indian Ocean - Puchen Zhao; Zhaocai Wu; Xiqiu Han; Yejian Wang; Jialing Zhang; Qiang Wang (Journal of Marine Science and Engineering)
Seafloor hydrothermal vent areas are potential sources of polymetallic sulfide deposits and exhibit distinct mineralization structures under different tectonic settings. The Daxi Vent Field (DVF), located on the Carlsberg Ridge in the northwestern Indian Ocean, represents a basalt-hosted hydrothermal system. To investigate the alteration zone structure of the DVF, high-resolution near-bottom bathymetric and magnetic data were collected during the Chinese DY57 expedition in 2019. Based on the results of magnetic anomaly data processing, including reduction to a level surface and Euler deconvolution, the location and depth of the magnetic sources were identified. In addition, two 2.5D magnetic forward models crossing the active and inactive vent fields were constructed. The results indicate that the range of the alteration zone in the active vent at the DVF extends up to 120 m in width and 80 m in depth, while the hydrothermal deposit at the extinct vent on the northeastern side extends up to 220 m along the ridge axis with a thickness of 30 m.